Cost estimation of utility strikes: towards proactive management of street works. Issue 2 (26th July 2018) - Makana, Lewis O; Metje, Nicole; Jefferson, Ian; Sackey, Margaret; Rogers, Chris D F
Abstract : The true (full) cost of a utility strike incident is rarely known. Generally, only the direct costs are used to measure the impact of utility strikes; the wider indirect and social costs are rarely quantified in monetary terms. Moreover, no established methodology exists to address this gap in knowledge, while access to fully documented records often presents the greatest challenge. This paper presents research that for the first time has been given access to 16 fully detailed utility strike case studies in UK urban areas. The research has identified and assessed the impacts of these utility strikes and provided an objective estimation of their associated (total) costs. These costs consist of those paid directly by the utility owner (direct costs), those borne by third parties in the contractual agreement (indirect costs) and those borne by other parties not engaged in the contractual agreement (social costs). Although the richness lies in the detailed case studies, the aggregated findings from all 16 utility strike case studies indicate that the total cost ratio – the ratio of indirect and social costs to the direct cost of repair – is 29:1. Thus there is a very substantial impact, which to date has been largely neglected.